1990
DOI: 10.1128/cmr.3.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans strain delineation

Abstract: Candida albicans is a major opportunistic pathogen causing a wide spectrum of disease in human beings. Methods for strain delineation of this species to assess or predict virulence or to conduct epidemiologic or pathogenetic investigations have been developed. Although factors associated with virulence have been identified, there is no rapid system to quantitate them in a clinical laboratory. Therefore, many typing methods are based on variable phenotypic characteristics within this species including morphotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 119 publications
1
94
1
Order By: Relevance
“…A distinct feature of C. albicans is that different clinical isolates have various electrophoretic karyotypes, as described by Merz et al (1988) and others (for a rewiew, see Merz, 1990), and investigated in detail for the four clinical isolates, 3153A, 199 1). In addition to having varied electrophoretic karyotypes, these four clinical isolates also had distinct colonial morphologies, consistent with the result with spontaneous morphological mutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A distinct feature of C. albicans is that different clinical isolates have various electrophoretic karyotypes, as described by Merz et al (1988) and others (for a rewiew, see Merz, 1990), and investigated in detail for the four clinical isolates, 3153A, 199 1). In addition to having varied electrophoretic karyotypes, these four clinical isolates also had distinct colonial morphologies, consistent with the result with spontaneous morphological mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, such variation was considered to offer reasonable grounds for establishing strain differences that might be used in epidemiological work (Merz, 1990). However, it has become clear that single strains, either fresh isolates or stock cultures, may give rise to mutants with single and multiple alterations in their electrophoretic karyotypes and that the frequency of such spontaneous mutations may be high (Suzuki et al, 1989;Rustchenko-Bulgac et al, 1990 ;Rustchenko-Bulgac, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This karyotyping method should be useful in clinical applications for strain identification (Merz, 1990). It has been reported that a change in karyotype appears to be correlated with a change in colony morphology (Rustchenko-Bulgac et al, 1990; Suzuki et al, 1989) although a definitive relationship between phenotype and karyotype has yet to be determined.…”
mentioning
confidence: 99%
“…With the advent of molecular genetics, the methods based on genotype (DNA) or variations in DNA structure have been applied to elucidate.the differences both among and within the species of medically important yeasts. These approaches are to detect differences between strains (i) in the restriction fragment length polymorphism of DNA (RFLP), occasionally in combination with Southern hybridization with specific DNA probes and (ii) in the electrophoretic karyotype (9,13).…”
mentioning
confidence: 99%